The Effect of a Fruit-Based Antioxidant Intervention on Depressive and Anxiety Symptoms in Postpartum Mothers: A Quasi-Experimental Study - Palupi, Khairizka Citra; Mulyadewi, Zalfa; Fadhilah, Reza; Melani, Vitria; Siahaan, Maya Fernandya; Marsidi, Siti Rahmah (Media Publikasi Cendekia Indonesia, 2025)
Depression and anxiety are common mental health issues affecting an 300 million people globally, with up to 13% of postpartum mothers experiencing depression and 19,8% with higher risks. These conditions can negatively impact both mother and child. The intake of natural antioxidants found in fruits has the potential to reduce these symptoms. This study aimed to analyze the effect of fruit consumption as a natural source of antioxidants on symptoms of depression and anxiety in postpartum mothers with children aged 1–12 months. The study was conducted from June-July 2024 in Bojong Rawalumbu, Bekasi City, using a quasi-experimental design with 64 respondents (28 in the treatment group and 29 in the control group completing the study). The treatment group received fruit interventions for 21 days, while the control group received no intervention. Depression symptoms were measured using the Edinburgh Postnatal Depression Scale (EPDS), anxiety levels were measured using the State-Trait Anxiety Inventory (STAI), and fruit consumption compliance was monitored using a provided form. The results showed a reduction in the mean depression score (difference of 2.00) and anxiety score (difference of 4.18) in the treatment group (p = 0.0001 for both). In conclusion, adequate fruit consumption may reduce symptoms of depression and anxiety in postpartum mothers with children aged 1–12 months.